Prognosis and immune response of a cuproptosis-related lncRNA signature in low grade glioma - Xu, Yifan; Wang, Chao; Li, Shifang; Zhou, Han; Feng, Yugong (Frontiers in Genetics, 2022)
Cuproptosis is a newly discovered new mechanism of programmed cell death, and its unique pathway to regulate cell death is thought to have a unique role in understanding cancer progression and guiding cancer therapy. However, this regulation has not been studied in LGG at present. In this study, data on LGG patients were downloaded from the TCGA database. We screened the genes related to cuproptosis from the published papers and confirmed the lncRNAs related to them. We applied univariate/ multivariate, and LASSO regression algorithms, finally identified 11 lncRNAs for constructing prognosis prediction models, and constructed a risk scoring model. The reliability and validity test of the model indicated that the model could well distinguish the prognosis and survival of LGG patients. Furthermore, the analyses of immunotherapy, immune microenvironment, as well as functional enrichment were also performed. Finally, we verified the expression of these six prognostic key lncRNAs using PCR and the TCGA database. In conclusion, this study is the first analysis based on cuproptosis-related lncRNAs in LGG and aims to open up new directions for AML therapy.